Harnessing photosynthesis to produce electricity using cyanobacteria, green algae, seaweeds and plants - Shlosberg, Yaniv; Schuster, Gadi; Adir, Noam (Frontiers in Plant Science, 2022)
The conversion of solar energy into electrical current by photosynthetic organisms has the potential to produce clean energy. Life on earth depends on photosynthesis, the major mechanism for biological conversion of light energy into chemical energy. Indeed, billions of years of evolution and adaptation to extreme environmental habitats have resulted in highly efficient light-harvesting and photochemical systems in the photosynthetic organisms that can be found in almost every ecological habitat of our world. In the harnessing photosynthesis to produce green energy approach, native photosynthesis is interfaced with electrodes and electron mediators to yield bio-photoelectrochemical cells (BPECs) that transform light energy into electrical power. BPECs utilizing plants, seaweeds, unicellular photosynthetic microorganisms, thylakoid or purified complexes, have been studied in attempts to construct efficient and non-polluting BPECs to produce electricity or hydrogen for use as green energy. The high efficiency of photosynthetic light-harvesting and energy production in the mostly unpolluting processes that make use of water and CO2 and produce oxygen beckons to develop this approach. On the other hand, the need to use physiological conditions, the sensitivity to photoinhibition, other abiotic stresses, and the requirement to extract electrons from the system, are challenging. In this review, we describe the principles and methods of the different kinds of BPECs that use natural photosynthesis, with an emphasis on BPECs containing living oxygenic photosynthetic organisms. We start with a brief summary of BPECs that use purified photosynthetic complexes. This strategy has produced high-efficiency BPECs. However, the lifetimes of operation of these BPECs are limited and the preparation is laborious and expensive. We then describe the use of thylakoid membranes in BPECs which requires less effort and usually produces high currents but still suffers from the lack of ability to self-repair damage caused by photoinhibition. This obstacle of the utilization of photosynthetic systems can be significantly reduced by using intact living organisms in the BPEC. We thus describe here progress in developing BPECs that make use of cyanobacte-ria, green algae, seaweeds and higher plants. Finally, we discuss the future challenges of producing high and longtime operating BPECs for practical use.